APPLICATION OF THE FOUR BUDDHIST PRINCIPLE OF SANGAHAVATTHU TO THE ADMINISTRATIONS OF MORARITY IN THE NEXT NORMAL AFFECTING THE QUALITY OF WORKING LIFE OF TEACHERS IN SCHOOLS UNDER CHANTHABURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Thamuang, Narongkorn; Warabamrungkul, Theerangkoon; Chansongsaeng, Arungiat (Journal of MCU Nakhondhat, 2024)
This research aims to: 1) Examine the application of the four Sangahavatthu principles by moral administrators under the Office of Chanthaburi Primary Educational Service Area 1; 2) Assess the quality of work life of teachers during the "next normal" period under the same office; 3) Explore the relationship between the application of the four Sangahavatthu principles by moral administrators and the quality of work life of teachers during the next normal; and 4) Develop a predictive model for the application of the four Sangahavatthu principles by moral administrators that affects the quality of work life of teachers during the next normal period. This is a quantitative research study using a questionnaire as the research tool. The sample group consisted of 306 individuals. Data were analyzed using mean, standard deviation, Pearson’s correlation coefficient, and simple regression analysis. The findings reveal that: 1) Moral administrators’ overall application of the four Sangahavatthu principles is at a high level. 2) The overall quality of work life of teachers during the next normal is also high. 3) There is a statistically significant relationship at the .01 level between the application of the four Sangahavatthu principles by moral administrators and the quality of work life of teachers during the next normal. and 4) The prediction of the applying the four Sangahavatthu principles by moral administrators significantly affects the quality of work life of teachers during the next normal at the .01 level. The raw score prediction equation is = 0.348 + 0.72**X. The standardized score prediction equation is: = 0.85**Zx. These results indicate that the application of the four Sangahavatthu principles by moral administrators has a significant effect on the quality of work life of teachers during the next normal, as hypothesized.